Analysis Of The Effect Of Capital Structure And Profitability On The Value Of Risk And Company Value (Case Study on Real Estate and Property Companies Listed on the Indonesia Stock Exchange in 2020-2022) - Suryanata, I Gusti Ngurah Putra (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the impact of capital structure and profitability on company value, as well as explore the relationship with the level of risk. Research is also to find out whether better management in capital structure and profitability can reduce company risk. The location of research was conducted in the real estate and property industry on the Indonesia Stock Exchange. The research sample was 44 companies within a period of 3 years of the annual publication of financial statements (time series). The analysis tool used is the Partial Least Square (PLS)-based SEM method requires 2 stages to assess the Fit Model of a research model. The results show that for the company's performance and future projections, an effective and transparent communication strategy with shareholders and investors is needed, involving risk disclosure, comprehensive risk analysis, technology utilization, and active involvement in corporate decision-making. Companies need diversification, regular communication with investors, mature risk management strategies, product innovation, transparent financial statements, and consideration of external cooperation to achieve a balance between profit and investment that is attractive to investors who care about risk and future projections. To overcome bankruptcy risk and achieve a balanced capital structure, companies need to implement a comprehensive approach by conducting risk analysis, business diversification, careful cash management, avoiding overleverage, and focusing on sustainable growth. Evaluate appropriate capital requirements for sustainable growth, combine multiple funding sources, have a phased growth plan, sound debt management, careful debt repayment planning, consider the impact of financial decisions on profitability, and maintain long-term stability.